2021
DOI: 10.3389/fnbeh.2021.698501
|View full text |Cite
|
Sign up to set email alerts
|

Complex Housing, but Not Maternal Deprivation Affects Motivation to Liberate a Trapped Cage-Mate in an Operant Rat Task

Abstract: Early life environment influences the development of various aspects of social behavior, particularly during sensitive developmental periods. We studied how challenges in the early postnatal period or (early) adolescence affect pro-social behavior. To this end, we designed a lever-operated liberation task, to be able to measure motivation to liberate a trapped conspecific (by progressively increasing required lever pressing for door-opening). Liberation of the trapped rat resulted either in social contact or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…On the other hand, 44-kHz calls were likely omitted as the analyses were restricted to canonical groups, i.e. flat 22-kHz and short 50-kHz calls, with a sharp dividing frequency border between the two (e.g., Kalamari et al, 2021, Potasiewicz et al, 2020, Turner et al, 2019) or even a frequency ‘safety gap’ between 22-kHz and 50-kHz vocalizations (e.g., Silkstone and Brudzynski, 2019, Garcia et al, 2015). Moreover – many older bat-detectors had limited frequency-range detection (e.g., up to 40 kHz in Sales, 1991), when stress-evoked types of ultrasonic calls were being established.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, 44-kHz calls were likely omitted as the analyses were restricted to canonical groups, i.e. flat 22-kHz and short 50-kHz calls, with a sharp dividing frequency border between the two (e.g., Kalamari et al, 2021, Potasiewicz et al, 2020, Turner et al, 2019) or even a frequency ‘safety gap’ between 22-kHz and 50-kHz vocalizations (e.g., Silkstone and Brudzynski, 2019, Garcia et al, 2015). Moreover – many older bat-detectors had limited frequency-range detection (e.g., up to 40 kHz in Sales, 1991), when stress-evoked types of ultrasonic calls were being established.…”
Section: Discussionmentioning
confidence: 99%
“…In the author's opinion, asserting that pro-social functioning is a correct description of door opening in the social release paradigm does not take into consideration the previously mentioned critical papers (e.g. [11,13,14,20]). This becomes more concerning in their follow-up paper where there is no commentary at all on the controversy concerning why rats release trapped conspecifics [27].…”
mentioning
confidence: 93%
“…The authors proposed that opening to release the soaked rat was pro-socially motivated [18], but once again critical voices presented another explanation that did not rely on an inference of empathy [19]. This time Schwartz et al [19] showed that the release of the trapped rat was maintained by '(a) the social contact offered by the released rat, and (b) the reinforcing value of proximity to a pool of water' ( [20], abstract). In other words, both Schwartz et al [19] and Silberberg et al [12] showed the importance of social reinforcement within different variants of the social release paradigm.…”
mentioning
confidence: 99%
See 2 more Smart Citations